In vitro cytotoxic activity of microalgal extracts loaded nano-micro particles produced via electrospraying and microemulsion methods - Karakas, Canan Y.; Sahin, Hande Tekarslan; Inan, Benan; Ozcimen, Didem; Erginer, Yildiz O. (WILEY, 2019)
Reactive oxygen species can bind protein, DNA, lipids, and carbohydrates and thus cause an oxidation reaction that induces various syndromes such as cardiovascular diseases, degenerative disease, and cancer types in the human body. Bioactive compounds, such as PUFA, EPA, DHA, and carotenoids in algae, have a chain ring and protect the tissue from chemical damage and reverse the symptoms of some diseases. Algal bioactives also have various biological properties such as anticoagulants, antiviral, antiangiogenic, antitumor, anti-inflammatory, antioxidant, antiproliferative, and immune modulation properties. This study aimed to show in vitro cytotoxic activity effect of Chlorella protothecoides and Nannochloropsis oculata microalgal extracts loaded nano-microparticles on A-172 (Homo sapiens brain glioblastoma) and HCT-116 (H. sapiens colon colorectal carcinoma) cell lines because of the increasing importance of algal biotechnology. MTT viability tests were performed on HUVEC, A172, and HCT 116 cells with particles obtained at optimum process parameters. The cell viability rates of encapsulated particles were also compared with pure algae extracts. Microalgal extracts loaded nano-micro particles showed very promising results for cytotoxic effect on cancer cells.
Keywords: anticancer effect; electrospraying; microalgae; microemulsion; nanotechnology; CHITOSAN NANOPARTICLES; THIOLATED CHITOSAN; MARINE MICROALGA; ALGINATE; POLYSACCHARIDES; PROLIFERATION; FABRICATION; NANOFIBERS; CULTURES; GELATION; Biotechnology & Applied Microbiology; Food Science & Technology